Ultrathin and Wearable Microtubular Epidermal Sensor for Real‐Time Physiological Pulse Monitoring. Issue 5 (10th April 2017) - Xi, Wang; Yeo, Joo Chuan; Yu, Longteng; Zhang, Shuai; Lim, Chwee Teck
Abstract : A flexible, stretchable, soft, and ultrathin wearable microtubular sensor that is highly sensitive to mechanical perturbations is developed. The sensor comprises a unique architecture consisting of a liquid‐state conductive element core within a soft silicone elastomer microtube. The microtubular sensor can distinguish forces as small as 5 mN and possesses a high force sensitivity of 68 N −1 . The microtubular sensor occupies a tiny footprint of 120 µm in diameter, approximately the cross‐section of a strand of hair. Superior sensing capabilities of the sensor are reported to detect perturbations from pulsatile air flows and demonstrate its applicability in continuous and imperceptible real‐time monitoring of arterial pulse waves. Abstract : A soft, flexible microtubular sensor for unobtrusive pulse monitoring is reported. A liquid metallic alloy is sealed within a microtube which is as thin as a strand of human hair to form the physical force sensor. The entire sensor is hardly distinguishable with the naked eye and can be used for the continuous monitoring of physiological signals.